Essays on political accountability and selection - Carrillo-Viramontes, Jose Antonio (2018)
The aim of this thesis is to contribute to the political agency literature by analysing theoretically how media can enhance political accountability and selection. In this thesis, I identify and analyse two channels in which media can affect political accountability and selection. First, media spillovers can improve voters' imperfect information and promote politicians' discipline. Second, journalism can affect the distribution of candidates' quality across levels of government. The thesis is composed of three chapters.